2020
DOI: 10.1007/s00227-020-03740-8
|View full text |Cite
|
Sign up to set email alerts
|

A quarter-century of variation in sponge abundance and community structure on shallow reefs in St. John, US Virgin Islands

Abstract: This study tested the hypothesis that sponge assemblages on the reefs of St. John, US Virgin Islands (18.315°N, 64.716°W), changed from 1992 to 2017. Sponges were identified to species or genus in photoquadrats and were quantified at 2-3 y intervals by density, with linear dimensions used to estimate volume as a proxy for biomass. From 1992 to July 2017, overall sponge density (pooled among taxa) increased, although trends varied among the most common species for which density increased (four species), decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Popular acceptance of the notion that sponges are increasing and growing over corals and reefs appears to be based on a few studies of increases (number of individuals or percent cover) in one or a few species (review in Wulff 2016, Edmunds et al 2020), in combination with a proposed mechanism of fast‐growing palatable sponges growing uncontrolled where spongivores are scarce (Loh and Pawlik 2014). Plausibility has been added by an apparent parallel with macroalgae increasing where herbivores are scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Popular acceptance of the notion that sponges are increasing and growing over corals and reefs appears to be based on a few studies of increases (number of individuals or percent cover) in one or a few species (review in Wulff 2016, Edmunds et al 2020), in combination with a proposed mechanism of fast‐growing palatable sponges growing uncontrolled where spongivores are scarce (Loh and Pawlik 2014). Plausibility has been added by an apparent parallel with macroalgae increasing where herbivores are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Even more awkward than a flawed mechanism to explain sponge increases on coral reefs is the lack of data documenting sponge increases on coral reefs. No extended time‐series studies of entire coral reef sponge faunas have demonstrated sponge biomass increases (reviews in Wulff 2016, Edmunds et al 2020), and, perhaps by coincidence, data from the few repeatedly censused sites in which sponges of all species were measured for volume, have identified declines in sponges, sometimes in the form of mass mortalities (Butler et al 1995, Wulff 2006 a , 2013, Stevely et al 2011; Biggs, B.C. and Strimaitis, A.M., unpublished manuscript ).…”
Section: Discussionmentioning
confidence: 99%
“…Like juvenile greens (Chambault et al 2020), hawksbills show spatial resilience to seasonal (Matley et al 2020) and extreme (Matley et al 2019) environmental fluctuations in BBHC; however, the chronic physiological impacts may still be detrimental. Furthermore, with ongoing climate change trends in the Western Caribbean, such as ocean warming and increased coral disease (Harvell et al 2004;Smith et al 2016), leading to loss of preferred habitat (e.g., coral reefs; Alvarez-Filip et al 2009;Smith et al 2013;Hughes et al 2018) and food sources (e.g., sponges; Edmunds et al 2020;Gochfeld et al 2020), resource use patterns will likely change if a critical point is reached. Therefore, gaining current knowledge of localized and long-term habitat and space use trends is important as a baseline to track and adapt to future changes in resource use.…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies of storm impacts have largely focused on scleractinian corals (Edmunds, 2019;Gardner et al, 2005;Gouezo et al, 2015;Harmelin-Vivien, 1994;Madin et al, 2012;Massel & Done, 1993), with fewer evaluating impacts on other benthic organisms, such as sponges or octocorals (Álvarez-Filip & Gil, 2006;Easson et al, 2013;Gochfeld et al, 2020;Lasker et al, 2020;Wulff, 1995). These reports suggest that powerful storms reduced sponge (phylum Porifera) species richness and biomass (Álvarez-Filip & Gil, 2006;Easson et al, 2013;Edmunds et al, 2020;Gochfeld et al, 2020;Wulff, 1995). Wulff (1995) reported that losses of Caribbean coral reef sponges due to Hurricane Joan in 1998 were dramatic, reducing combined density of the three most common species by nearly half (Wulff, 1995), whereas Easson et al (2013) found through the monitoring of sponge individuals that A. cauliformis populations were reduced by ~20% following Hurricane Irene.…”
Section: Introductionmentioning
confidence: 99%